Spatial Variation in Thermal Stress Experienced by Barnacles on Rocky Shores: The Interplay Between Geographic Variation, Tidal Cycles and Microhabitat Temperatures - Wang, Hui-Yu; Tsang, Ling Ming; Lima, Fernando P.; Seabra, Rui; Ganmanee, Monthon; Williams, Gray A.; Chan, Benny K. K. (Frontiers in Marine Science, 2020)
Thermal stress is an important driver of species’ distribution in the intertidal zone and, with the forecasted increasing frequency of extreme high temperatures associated with climate change, is likely to play an even greater role in the future. To better understand the scales at which thermal stress impacts organisms, we used biomimetic temperature loggers (robobarnacles) to measure latitudinal variation in estimated barnacle body temperatures (Tetraclita spp.) and evaluated the influences of large, geographic, and smaller scale, microhabitat variation on temperatures experienced. Robobarnacles were deployed at nine sites along the West Pacific and South China Sea coast (five sites in Taiwan, three in Hong Kong and one in Thailand, spanning 13-25 N) from May to September 2013. Estimated body temperatures did not follow a latitudinal gradient; instead, they revealed a mosaic of hot (e.g., NE Taiwan and Thailand) and cooler sites (e.g., two sites in Hong Kong). The hot sites were characterized by frequent occurrences of ‘heat stress’ events (estimated body temperatures  40C for  2 hours which would result in  50% Tetraclita entering coma). There was a correlation between hourly air temperatures and robo-temperatures, suggesting that air temperature together with solar radiation and thermal radiation re-emited by the rocky substrate drove the observed spatial robo-temperature variation. Air temperature is, therefore, an important contributor in affecting the body temperature of sessile intertidal species in the tropical and subtropical W Pacific and South China Sea and can be a good predictor for body temperature and thermal stress of intertidal barnacles.